Lier la recherche en milieu urbain avec l’approche « livelihood » : défis et perspectives - Brigit Obrist (Éditions en environnement VertigO, 2006)
Linking a livelihood approach with urban health research allows for important achievements in terms of research and action. A conceptual framework separating vulnerability in three dimensions – commoditization, environmental hazards and social fragmentation – allows deepening the understanding on urban health problems. Based on a series of case studies in West Africa, this paper argues that new starting points and concepts rise through linking risk and vulnerability approaches – specifically those focused on access to basic services as health and education – with resilience.